Ruthenium Triazine Composite: A Good Match for Increasing Hydrogen Evolution Activity through Contact Electrification. Issue 21 (16th April 2020) - Ju, Qiangjian; Ma, Ruguang; Pei, Yu; Guo, Beibei; Li, Zichuang; Liu, Qian; Thomas, Tiju; Yang, Minghui; Hutchings, Graham J.; Wang, Jiacheng
Abstract: The development of Pt‐free catalysts for the alkaline hydrogen evolution reaction (HER), which is widely used in industrial scale water‐alkali electrolyzers, remains a contemporary and pressing challenge. Ruthenium (Ru) has excellent water‐dissociation abilities and could be an alternative water splitting catalyst. However, its large hydrogen binding energy limits HER activity. Here, a new approach is proposed to boost the HER activity of Ru through uniform loading of Ru nanoparticles on triazine‐ring (C3 N3 )‐doped carbon (triNC). The composite (Ru/triNC) exhibits outstanding HER activity with an ultralow overpotential of ≈2 mV at 10 mA cm −2 ; thereby making it the best performing electrocatalyst hitherto reported for alkaline HER. The calculated metal mass activity of Ru/triNC is >10 and 15 times higher than that of Pt/C and Pt/triNC. Both theoretical and experimental studies reveal that the triazine‐ring is a good match for Ru to weaken the hydrogen binding on Ru through interfacial charge transfer via increased contact electrification. Therefore, Ru/triNC can provide the optimal hydrogen adsorption free energy (approaching zero), while maintaining the strong water‐dissociation activity. This study provides a new avenue for designing highly efficient and stable electrocatalysts for water splitting. Abstract : A triazine‐ring as an active "electron acceptor" is a good match for ruthenium to weaken hydrogen's binding to ruthenium through interfacial charge transfer via increased contact electrification. This is confirmed by both theoretical and experimental results. The resulting ruthenium triazine composites exhibit outstanding hydrogen evolution reaction activity when compared to commercial Pt/C in alkaline solution.